Prevalência de cepas resistentes a antibióticos no solo, água, e vegetais, sob influência de dejetos de animais - Fanton, Eliane Aparecida de Souza (2021)
Dieases caused by microorganisms resistant to antibiotics already surpass 700 thousand deaths per year, this number could rise to more than ten million deaths per year by 2050, causes the increase in health spending, and can lead more than 24 million people to extreme poverty by 2030. Antimicrobial resistance is a public health problem that worries leaders worldwide and grows at alarming levels, where the causes can be controlled by the conscious and correct use of ntimicrobials. One of the effects that most concern health leaders is the use of antimicrobial in the animal diet for growth promotion and diease prevention, this fact is even more worrying because 80% of these drugs are excreted because they are metabolized. The present study verified the prevalence of microorganisms resistant to antibiotics in the waste of domestic animals (birds, swine and cattle), in the soil, in the fertilized vegetables an in the adjacent waters by the microbiologicals culture method using diffusion discs. Of the three drugs tested for resistance, the most efficient was tetracycline at 30 ug, followed by streptomycin 10 ug, with penicillin 10 ug being the least indicated drug to be used, where 61,11% of the analyzed samples showed resistance to this antibiotic. The persistence of resistant pathogens in fresh fruit and vegetables after cleaning and pre-asepsis using 70% alcohl and 2,5% sodium hypoclorite, was proven in at least of the antibiotics examined in 100% of the tested samples